Geo-Archaeological endowments and the tourism development in Eritrea - Afsar Alam, Mohammad; Mishra, Niraj Kumar (Journal for Geography, 2013)
Eritrea is one of the countries located in the horn of Africa. Geo-Archaeological sites of the country have been the main focus of the study area. This paper presents an overview of the research and includes a discussion of the tourism potential of Eritrea and potential benefits of Geo-Archaeological endowments in the development of its tourism industry. She is having diverse Geo-Archaeological endowments which are capable of attracting large number of tourists from all over the world. This country enjoys unique and exciting landmarks, such as breath-taking escarpments, mountains, depressions, open plains, plateaus, Sea with immense variety of marine life, islands, beautiful coastal lines etc. Furthermore, as Eritrea is situated in the region of the cradle of life, it owns rare archaeological and historical sites with unraveled cultural heritages. Though, Eritrea’s tourism industry is currently rated as one of the lowest foreign exchange earners in the country, the potential of tourism industry to become a leading source of foreign exchange earnings in Eritrea has not been far realized. It is evident that the country’s tourism potential has not been fully explored and marketed. Though several attempts have been made to enhance its rapid development, but these efforts have suffered some major drawbacks i.e. because the richness of the sites is not fully exploited to such an extent that it can revitalize the tourism sector and due to lack of a comprehensive spatial database of tourism facilities and destinations. In the present paper an attempt has been made to investigate the role of Geo-Archaeological Sites in the Development of Tourism with respect to tourism potentials in the country.